KEBIJAKAN SEKTOR HULU DAN HILIR GAS BUMI DALAM RANGKA MEMENUHI KEBUTUHAN DALAM NEGERI - Sahat Aditua Silalahi; Ariesy Tri Mauleny (Pusat Penelitian, Badan Keahlian DPR RI, 2011)
Natural gas shall play an important role in national energy needs mainly due tothe scarcity of petroleum reserves. The government shall formulate policies inboth the upstream and downstream sides that support the paradigm of naturalgas utilization for domestic purposes. On the upstream side, the long chain ofbureaucracy needs to be cut in order to create a more conducive investmentclimate. Meanwhile, on the downstream side, the government should acceleratethe infrastructure development for natural gas transmission and distribution.The availability of this infrastructure is vital in order to distribute the natural gasto consumers. To strengthen the downstream sector, the most important issue isto release the dependency of consumption by the industrial sector.Revitalization program especially on city gas and fuel gas is a strategy that canbe taken in order to expand the use of natural gas in households andtransportation sectors.